2011
DOI: 10.1063/1.3549201
|View full text |Cite
|
Sign up to set email alerts
|

Subgap optical conductivity in semihydrogenated graphene

Abstract: We report that for graphene with a finite band gap (such as semihydrogenated graphene or graphene with spin-orbit coupling), there exists a strong nonlinear optical response for energies lower than the band gap where the linear response is forbidden. At low temperatures, the nonlinear current in graphene with a gap is much stronger than that in gapless graphene. Our result suggests that semihydrogenated graphene can have a unique potential as a two-color nonlinear material in the terahertz frequency region. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…Unfortunately, nonlinear optical effects in conventional semiconductors are usually minimal unless an extremely intense laser pulse is applied, and this greatly reduces the practicality of semiconductor-based devices. Recently, it has been demonstrated that the nonlinear optical response in graphene and several sister structures can be rather strong, especially in the important terahertz frequency regime [15][16][17][18][19][20][21][22][23]. For single layer graphene, strong terahertz interband [15] and intraband [16,17] nonlinear optical responses were theoretically predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, nonlinear optical effects in conventional semiconductors are usually minimal unless an extremely intense laser pulse is applied, and this greatly reduces the practicality of semiconductor-based devices. Recently, it has been demonstrated that the nonlinear optical response in graphene and several sister structures can be rather strong, especially in the important terahertz frequency regime [15][16][17][18][19][20][21][22][23]. For single layer graphene, strong terahertz interband [15] and intraband [16,17] nonlinear optical responses were theoretically predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbative models are developed to supplement the interband physics, for example the quantum mechanical (QM) Dirac equation model [61,62,64,66,67,89], and also the semiconductor Bloch equations [73,75,76,85]. The QM model replaces v g in equation (3.1) with v g = ψ|∂ H/∂k|ψ , where ψ is the wave function of graphene and H is the Dirac Hamiltonian, which replaces N(p) with N(p) = f (−ε k ) − f (ε k ), the Fermi distribution difference between the conduction and valence bands.…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%
“…The optical properties of graphene have been studied both experimentally [9][10][11][12][13][14][15][16][17] and theoretically [18][19][20][21][22][23][24][25][26][27][28][29][30]. In the terahertz to the far-infrared (FIR) spectral regime, optical conductance of graphene-based systems attracts many researchers' interests due to the ongoing search on viable terahertz detectors and emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [25] also treated the same topic with more rigorous perturbation theory. Yee Sin Ang et al [28,29] investigated the optical conductivity of SHG and KP graphene superlattic. It has been shown that SHG possesses a unique potential as a two-color nonlinear material and the total optical response of the graphene superlattice was enhanced due to the formation of anisotropic Dirac fermions in the terahertz frequency region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation